Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x^4 - y^4
= (x^2 - y^2)(x^2 + y^2)
= (x - y)(x + y)(x^2 + y^2)
\(x^4+x^3y-xy^3-y^4=x^3\left(x+y\right)-y^3\left(x+y\right)\)
\(=\left(x+y\right)\left(x^3-y^3\right)=\left(x+y\right)\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(x^4+y^4+\left(x+y\right)^4\)
\(=x^4+y^4+\left(x^2+2xy+y^2\right)^2\)
\(=x^4+y^4+x^4+6x^2y^2+y^4+4x^3y+4xy^3\)
\(=2.\left(x^2+y^2\right)^2+4xy\left(x^2+y^2\right)+2x^2y^2\)
\(=2.\left(x^2+y^2\right)\left(x^2+y^2+2xy\right)+2x^2y^2\)
\(=2.\left[\left(x^2+y^2\right)\left(x+y\right)^2+x^2y^2\right]\)
Sai thì thôi nhé~
\(x^4+y^4+\left(x+y\right)^4\)
\(=x^4+y^4+x^4+4x^3y+6x^2y^2+4xy^3+y^4\)
\(=2x^4+4x^3y+6x^2y^2+4xy^3+2y^4\)
\(=2\left(x^4+2x^3y+3x^2y^2+2xy^3+y^4\right)\)
\(=2\left[\left(x^4+2x^3y+x^2y^2\right)+2\left(x^2+xy\right)y^2+y^4\right]\)
\(=2\left[\left(x^2+xy\right)^2+2\left(x^2+xy\right)y^2+\left(y^2\right)^2\right]\)
\(=2\left(x^2+xy+y^2\right)^2\)
\(4x^4+y^4\)
\(=4x^4+4x^2y^2+y^4-4x^2y^2\)
\(=\left(2x^2+y^2\right)^2-\left(2xy\right)^2\)
\(=\left(2x^2-2xy+y^2\right)\left(2x^2+2xy+y^2\right)\)